2004
DOI: 10.1155/2005/460983
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Hepatitis A in Children in British Columbia

Abstract: Children in nonurban areas of British Columbia are generally at low risk of HAV infection during the first decade of life regardless of the reported population rates, thereby permitting the consideration of school-based HAV immunization programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
(17 reference statements)
2
3
0
Order By: Relevance
“…The relatively high prevalence of anti-HAV among nonvaccinated individuals resulted mainly from individuals born outside Canada, as the rate in Canadian-born subjects was only 8.8%. The greater prevalence of anti-HAV in Canadian-born individuals in their late thirties than in their early twenties is consistent with our earlier reports 8,10 that hepatitis A is relatively uncommon among children and suggests that young adults are at substantial risk. Our data also support earlier reports 10,15 that foreign travel is an important risk factor for Canadians.…”
Section: Age (Years)supporting
confidence: 90%
See 2 more Smart Citations
“…The relatively high prevalence of anti-HAV among nonvaccinated individuals resulted mainly from individuals born outside Canada, as the rate in Canadian-born subjects was only 8.8%. The greater prevalence of anti-HAV in Canadian-born individuals in their late thirties than in their early twenties is consistent with our earlier reports 8,10 that hepatitis A is relatively uncommon among children and suggests that young adults are at substantial risk. Our data also support earlier reports 10,15 that foreign travel is an important risk factor for Canadians.…”
Section: Age (Years)supporting
confidence: 90%
“…The greater prevalence of anti-HAV in Canadian-born individuals in their late thirties than in their early twenties is consistent with our earlier reports 8,10 that hepatitis A is relatively uncommon among children and suggests that young adults are at substantial risk. Our data also support earlier reports 10,15 that foreign travel is an important risk factor for Canadians. While the number of anti-HAV-positive individuals and the number reporting travel to the developing world for more than 2 weeks at a time were relatively few, it is worth noting that 60% of Canadian-born, non-vaccinated individuals with anti-HAV reported such travel.…”
Section: Age (Years)supporting
confidence: 90%
See 1 more Smart Citation
“…A total of 36 reports describing 34 unique studies were included in the systematic review (Table 1) [18,19,22-55]. These were obtained from screening 413 potentially relevant citations and reviewing 66 full-text study reports and 25 public health reports (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…There was no association between seropositivity and gender based on 9 population comparisons from 5 studies (n = 4158, URR: 1.0 [95% CI: 0.9, 1.1]) [22,31,35,41,54], which was consistent with results of 3 other studies reporting adjusted risk estimates (Table 3) [25,34,48]. Two studies in the early 1980's suggested that individuals living in urban areas were 30% more likely to have HAV antibody compared to those in rural areas (n = 647, URR: 1.3 [1.2, 1.5]) [41,46].…”
Section: Resultsmentioning
confidence: 99%